Back-Calculation of Total Lengths of Luciobarbus mystaceus (Pallas, 1814) from Scale and Otolith Measurements - Çalta, Metin; Teksar, Can (Fırat University, 2019)
In this study, the total lengths of Luciobarbus mystaceus species at previous ages were estimated from scale and otolith lengths by using back-calculation methods. For this purpose, 20 fish samples with 4-7 years in age, 37.1-47.4 cm in total length and 426.1-874.1 g in weight were obtained from a commercial fisherman in Keban Dam Lake. By using the back-calculation methods, the mean total length values for each ages calculated from scale lengths and otolith lengths were calculated as L1=7.7, L2=14.9, L3=21.4, L4=28.1, L5=30.3, L6=33.5, L7=35.7 cm and L1=7.5, L2=14.5, L3=19.2, L4=26.3, L5=29.6, L6=33.3, L7=33.9 cm respectively. The total lengths of fish calculated from scale and otolith measurements for all age groups were always determined smaller than observed total lengths of fish. There was a significant differences between calculated and observed lengths, but did not differ between total fish lengths calculated from scale and otolith measurements.
Keywords: Engineering; Mühendislik